2015
DOI: 10.1002/jbm.a.35477
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of polymer‐derived ceramics for pacemaker electrode applications

Abstract: Ceramics are known to be chemically stable, and the possibility to electrically dope polymer-derived ceramics makes it a material of interest for implantable electrode applications. We investigated cytotoxic characteristics of four polymer-derived ceramic candidates with either electrically conductive or insulating properties. Cytotoxicity was assessed by culturing C2C12 myoblast cells under two conditions: by exposing them to material extracts and by putting them directly in contact with material samples. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Therefore, a live/dead assay comprising several liquid exchanges and rinsing steps is too challenging. Nevertheless, the elongated shape of the cells is a strong indication of their vitality …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a live/dead assay comprising several liquid exchanges and rinsing steps is too challenging. Nevertheless, the elongated shape of the cells is a strong indication of their vitality …”
Section: Resultsmentioning
confidence: 99%
“…The stoichiometry of oxygen and carbon can be easily adjusted by different raw organosilicon polymers or chemical post-treatments, leading to a promising use for SiOC in blood-contact applications. Grossenbacher et al [148] demonstrated that the polymer-derived ceramics were stable and low toxicity, and their electrical conductivity could be adjusted by carbon doping, which could be used in implantable electrode applications such as pacemakers. Tamayo et al [149][150][151] fabricated mesoporous SiOC for controlled drug delivery.…”
Section: Wwwspringercom/journal/40145mentioning
confidence: 99%
“…Silicon carbonitride (SiCN) derived from polysilazane possesses the outstanding properties including thermal stability, high mechanical strength, and excellent fracture toughness, which shows great potential for high temperature and structure applications [153,154]. In general, amorphous SiCN ceramics can be obtained at 1000 ℃, which are transferred into SiC and Si 3 N 4 phases with free carbon at a higher temperature, and then β-SiC could be formed from the reaction between Si 3 N 4 and free carbon over 1800 ℃ [73,[147][148][149][150].…”
Section: Wwwspringercom/journal/40145mentioning
confidence: 99%
“…They have attractive high‐temperature mechanical properties, excellent oxidation resistance, and functional properties including semiconductivity, gas‐sensing, piezoresistivity, and lithium sequestration . Their biocompatibility harbors well for medical applications …”
Section: Introductionmentioning
confidence: 99%